مرحلة المفاوضة عند إبرام العقود الإدارية في ضو‌ء التعليمات النافذة في الإقليم و العراق - فارس, روقیە عثمان (Sulaimani Journal for Humanities, 2023)
The pre-contracting stage or the negotiation stage when concluding administrative contracts is a very important stage and at the same time an influential stage of discussions between the two parties (the administration and the party that wishes to contract with it). Before it becomes a contract, his stage must pass through a long stage of preparation, discussion and especially in administrative contracts of great financial importance, negotiation is based on discussion and opinions and bargaining begin between the administration party and the other party who wishes to contract with it in order to reach the contract, and negotiation takes place on the affirmation of the invitation announced by the administration. The aim of writing this research is to explain the negotiation of administrative contracts and the principles that govern this process, and to clarify the problematic of the legal organization for negotiating administrative contracts in the Kurdistan Region - Iraq in the context of a refereed research plan until the research reached its conclusion represented in the most prominent conclusions and the research results, as well as the proposals and recommendations put forward in it in order to fill the shortcomings and defects and develop that legal regulation.
Keywords: negotiation; Legal regulation administrative contracts